Analisis Dampak Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Amelia Rahmawati; Anggi Rahmawati; Sabrina Harum Insani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the extent to which tax sanctions affect the compliance level of motor vehicle taxpayers. Motor vehicle tax is one of the main sources of regional revenue that supports infrastructure development, education, and public services. However, many taxpayers still fail to fulfill their tax obligations on time due to a lack of awareness, insufficient understanding of the importance of taxes, and limited government socialization. This research uses a descriptive qualitative method by utilizing secondary data obtained from various literature sources and official publications related to the implementation of sanctions and taxpayer compliance levels. The analysis results show that the application of administrative sanctions, such as fines and penalties for late payments, has a positive and significant effect on improving taxpayer compliance. Nevertheless, the compliance that arises due to sanctions tends to be temporary and is mostly driven by fear of punishment rather than genuine awareness. Therefore, the effectiveness of sanctions should be complemented by tax education and continuous outreach programs to foster voluntary compliance. In conclusion, combining strict enforcement with the development of taxpayer awareness can create sustainable tax compliance and increase regional tax revenues.